2018
DOI: 10.1039/c8bm00807h
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial peptide modification enhances the gene delivery and bactericidal efficiency of gold nanoparticles for accelerating diabetic wound healing

Abstract: Impaired angiogenesis and bacterial infection have increasingly been implicated as the major causes of delayed diabetic wound healing. However, there is currently no effective therapy. Here, we optimized a novel gene delivery system based on antimicrobial peptide (LL37) grafted ultra-small gold nanoparticles (AuNPs@LL37, ∼7 nm) for the topical treatment of diabetic wounds with or without bacterial infection. AuNPs@LL37 combines the advantages of cationic AuNPs that condense DNA with those of antibacterial pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 63 publications
0
88
0
1
Order By: Relevance
“…In vivo, the intraperitoneal injection of AOA-2 (10 mg/kg) in combination with CST (10 mg/kg) improved the survival rate of mice with bacteraemia by 20% [72,73]. In addition, some classic antimicrobial peptides (AMPs) interacting with AbOmpA have been gradually discovered, which are a series of endogenous defense peptides to kill bacteria and fungus [74][75][76]. For example, bovine myeloid antimicrobial peptide (BMAP-28) and its analog peptides killed MDR-A.…”
Section: Therapeutic Strategies Targeting Abompa Polypeptidementioning
confidence: 99%
“…In vivo, the intraperitoneal injection of AOA-2 (10 mg/kg) in combination with CST (10 mg/kg) improved the survival rate of mice with bacteraemia by 20% [72,73]. In addition, some classic antimicrobial peptides (AMPs) interacting with AbOmpA have been gradually discovered, which are a series of endogenous defense peptides to kill bacteria and fungus [74][75][76]. For example, bovine myeloid antimicrobial peptide (BMAP-28) and its analog peptides killed MDR-A.…”
Section: Therapeutic Strategies Targeting Abompa Polypeptidementioning
confidence: 99%
“…In vitro study [17] Micro-nano bioactive glass particles In vitro study [31] Mesoporous silica nanoparticles In vitro study [32] Soft tissue wound healing Gold nanoparticles (1) In vitro study (2) In vivo wound model [14,38,43,44] Nano-sized bioactive glass (1) In vitro study (2) In vivo wound healing assay [39] Cerium oxide nanoparticle (1) In vitro study (2) In vivo wound model [42] the PCL nano-composite membranes incorporated with Zn-doped hollow mesoporous silica nanospheres…”
Section: Nanomaterials Type Of Angiogenesis Assays Referencesmentioning
confidence: 99%
“…On one hand, stress is supported by embedded nanofibres, so that the elasticity of matrix is reinforced. On the other hand, they have been demonstrated to improve the adhesion and proliferation of endothelial cells and promote angiogenesis [35][36][37][38].…”
Section: Skin Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the ability of Au NPs, based on antimicrobial peptide combined with pro-angiogenic (vascular endothelial growth factor (VEGF)) plasmids, to promote angiogenesis and inhibit bacterial infection in diabetic wounds, resulting in faster re-epithelization, improved granulation tissue formation and high VEGF expression. 103 Curcumin NPs were found to have strong antibacterial activity to suppress the growth of Pseudomonas aeruginosa and Staphylococcus aureus. 104 It was also demonstrated that curcumin NPs could reduce inflammation and induce cell expansion, which is useful in the reconstruction of damaged tissue.…”
Section: The Potential Use Of Nanoparticles In the Treatment Of Woundsmentioning
confidence: 99%